2015
DOI: 10.1371/journal.pone.0135712
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Lower Jaw Position on the Running Pattern

Abstract: IntroductionThe effects of manipulated dental occlusion on body posture has been investigated quite often and discussed controversially in the literature. Far less attention has been paid to the influence of dental occlusion position on human movement. If human movement was analysed, it was mostly while walking and not while running. This study was therefore designed to identify the effect of lower jaw positions on running behaviour according to different dental occlusion positions.MethodsTwenty healthy young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 51 publications
2
44
0
1
Order By: Relevance
“…In recent years, several publications have reported an improvement of performance through a change in jaw position [ 1 10 ]. Studies have even shown that short-term changes of the occlusion condition induces positive effects on postural control [ 11 16 ], body posture [ 17 22 ], walking and running patterns [ 9 , 23 – 25 ], endurance [ 8 ] and strength performance [ 1 , 3 , 5 , 7 , 10 ]. The myocentric position (the mandible has a balanced isotonic muscle contraction while clinching) has produced more stable postural positions when compared to maximal occlusion condition (habitually relation of the upper jaw to the lower jaw while maximum clenching), centric occlusion, where the jaw condyle is in a centric and rest position (no contact between upper and lower jaw) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, several publications have reported an improvement of performance through a change in jaw position [ 1 10 ]. Studies have even shown that short-term changes of the occlusion condition induces positive effects on postural control [ 11 16 ], body posture [ 17 22 ], walking and running patterns [ 9 , 23 – 25 ], endurance [ 8 ] and strength performance [ 1 , 3 , 5 , 7 , 10 ]. The myocentric position (the mandible has a balanced isotonic muscle contraction while clinching) has produced more stable postural positions when compared to maximal occlusion condition (habitually relation of the upper jaw to the lower jaw while maximum clenching), centric occlusion, where the jaw condyle is in a centric and rest position (no contact between upper and lower jaw) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Maurer et al [ 9 ] have reported increases in symmetry of kinematics during running. Improvements in endurance have been measured using Wingate test [ 3 ], sprints [ 5 ] and Cooper test [ 10 ] wearing custom-made mouth guards.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…oben). Die Abschlussmessungen werden nach dem gleichen Prinzip wie bei der Eingangsmessung, nach der 8-wöchigen Intervention, wiederholt.Der Funktionsstatus des Kiefergelenks wurde mittels eines an die DC/TMD angelehnten Tests untersucht, mit dem es möglich ist, temporomandibuläre Dysfunktionen herauszustellen.Nachdem alle Probandinnen für die Studie inkludiert wurden fand eine zufällige Zuordnung (Block-Randomisierung mit Briefumschlägen) der Studienteilnehmer in die Interventions-(Schienengruppe) oder Kontrollgruppe (Nicht-Schienengruppe) statt.Den Probandinnen der Schienengruppe wurde ein individuelles dentales Aufbiss-Behelf mittels Futar-Biss-Registratsmasse angefertigt (▶ Abb 4,5)…”
unclassified